Assessing vaccine hesitancy among health-care workers in Jammu and Kashmir: A cross-sectional study - Naveed Nazir Shah; Syed Quibtiya Khursheed; Zaid Khan; Shuja Reagu; Majid Alabdulla; Inaamul Haq; Shabir Ahmad Dar; Adnan Hamza; Khurshid Ahmad Dar; Syed Suraiya Farooq; Bikram Singh Datta (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The World Health Organization declared vaccine hesitancy as one of the planet's top 10 global health threats in 2019. With the rollout of the coronavirus disease-19 (COVID-19) vaccines, a survey was conducted to find out the hesitancy and the apprehensions that come along with taking COVID-19 vaccines among health-care workers (HCWs). MATERIALS AND METHODS: This was an online cross-sectional survey which was developed and shared through social media platforms among the HCWs of Kashmir. The survey captured demographic data and used a validated hesitancy measurement tool from January 2021 to February 2021. The data were analyzed by descriptive statistics and multivariable logistic regression using Stata 15 (Stata Corp. 2017. Stata Statistical Software: Release 15. College Station, TX: Stata Corp LLC). RESULTS: Willingness to take the COVID-19 vaccine when available was seen in 67.7% of the HCWs. Overall, 9.59% of respondents reported unwillingness to receive a vaccine for COVID-19, while 22.7% were unsure. The most commonly cited reason for willingness to get vaccinated was an understanding of the disease and vaccination, as reported by 81.5%. Being single was significantly related to an increased risk of vaccine hesitancy (adjusted odds ratio = 5.27, 95% confidence interval: 2.07-13.40). Among vaccine attitudes, concerns about the safety of the vaccine, unforeseen problems in children, and possible unknown future adverse effects of the vaccine were the most important determinants of unwillingness. CONCLUSIONS: A significant proportion of the HCWs showed vaccine hesitancy to the COVID-19 vaccine. Hesitancy attitudes were almost always driven by concern around the vaccine safety. States and health-care authorities need to recognize the massive trust deficit around the Covid-19 vaccine and use the popular media used by people to share credible and reliable information.